[Is there a solution to the drought? Recurrent water crises and the role of groundwater] - Rusi, Sergio; Alberti, Luca; Da Pelo, Stefania; De Filippis, Giovanna; Di Curzio, Diego; Forte, Giovanni; Lasagna, Manuela; Petitta, Marco; Piscopo, Vincenzo; Preziosi, Elisabetta; et al. (Acque Sotterranee - Italian Journal of Groundwater, 2022)
Not available [In Italian]